THE ROLE OF INDUSTRY IN THE ECONOMY AND ITS RELATIONSHIP WITH ECOLOGY, PROBLEMS AND SOLUTIONS - Ismoilov, Otajon (THE INNOVATION ECONOMY, 2026)
This article analyzes the role of the industrial sector in economic growth, mechanisms for minimizing environmental damage during industrialization, and the theoretical foundations of the transition to economically and environmentally sustainable development. The study highlights international models that express the relationship between economic efficiency and environmental sustainability, as well as strategies for modernizing the national economy.